2021
DOI: 10.1155/2021/3236892
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light from Cell Phones Can Cause Chronic Retinal Light Injury: The Evidence from a Clinical Observational Study and a SD Rat Model

Abstract: Background. To investigate the chronic photodamage induced by the low-intensity blue light of phones, we carried out a clinical pilot study and established an animal model by irradiating SD rats with a homemade illuminator. Methods. Clinical investigation: A total of 25 clinical medical workers in our hospital were selected and divided into a control group and an observation group according to the daily video terminal use time. Multifocal electrophysiological system (Mf-ERG) was used for retinal functional exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…This damage was illuminance-dependent, demonstrating the harmful effects of blue light, even without a resulting retinal cell death. Our findings are aligned with the clinical investigation of volunteers with daily terminal video usage cumulative time of over 8 h. This occupational exposure reduces the amplitude of retinal photoreceptors and delays the peak time [ 39 ]. Thus, the structural and functional damage of the retina induced by low-illuminance blue light warrants attention.…”
Section: Discussionsupporting
confidence: 86%
“…This damage was illuminance-dependent, demonstrating the harmful effects of blue light, even without a resulting retinal cell death. Our findings are aligned with the clinical investigation of volunteers with daily terminal video usage cumulative time of over 8 h. This occupational exposure reduces the amplitude of retinal photoreceptors and delays the peak time [ 39 ]. Thus, the structural and functional damage of the retina induced by low-illuminance blue light warrants attention.…”
Section: Discussionsupporting
confidence: 86%
“…Focusing their attention on VDTs as well, Li et al conducted a clinical observational study in which they observed the chronic photodamage induced by the low-intensity blue light of phones [ 48 ]. With the use of mfERG, they examined the response of several small retinal regions in the macular area of 25 healthy participants whose use of VDTs was high.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Previous studies have shown that the effect of blue light on the retina depends on the frequency bands. 43,44 In addition, blue light exposure induced apoptosis in RPE cells in vitro in durationand intensity-dependent manner, and 6-hour exposure to 2000 lux is the optimum condition for triggering photodamage in human RPE cells. 20,27 In this study, we successfully established an in vitro blue light damage model by irradiating rodent RPE cells with the light of wavelength range 440 AE 10 nM, and the optimum conditions were as previously described.…”
Section: Discussionmentioning
confidence: 99%